The Effect of Using The Picture and Picture Learning Model Assisted by The Pancasila Board On The Learning Outcomes of Pancasila Education In Grade 4 Elementary School - Septiani Putri Kinanti; Zulfadewina Zulfadewina (Dinasti International Journal of Education Management And Social Science, 2024)
Pancasila Education is still perceived as tedious and challenging. Based on the findings of these observations, it is evident that students' level of interest in Pancasila Education subjects remains relatively low. The teaching and learning process of Pancasila material sometimes relies solely on textbooks and the lecture approach, resulting in suboptimal classroom outcomes. This study employs quantitative methodologies. The objective of this study is to investigate if the utilization of Pancasila Board media in Pancasila Education has an impact on the learning outcomes of fourth-grade students. This study used a quasi-experimental research method known as the Quasi Experimental Design, specifically utilizing the "Post test Only Control Design". After analyzing the research data, it was found that the control class meeting achieved an average score of 69.417. This demonstrates that pupils' comprehension of the assessed topic is significantly deficient due to the continued inadequacy of media or instructional techniques. The outcomes of the experimental class, which received treatment in the form of learning via the Pancasila Board media, differ significantly when compared to other classes. The experimental group achieved an average score of 78.568 after receiving treatment.